Aktivitas Penangkapan Radikal 2,2-difenil-1-pikril hidrazil Fraksi Terhidrolisis Asam Daun Duwet (Syzigium cumini L.) dan Daun Nangka (Artocarpus heterophyllus) - Irianti, Tatang; Yasmin, Intan Farida; Astuti, Ratih Dwi; Purnomo, Hari (Jurnal Farmasi Udayana, 2024)
Plants contain secondary metabolites, including flavonoids, whose molecules are still bound to glycosides or are not free molecules. Hydrolysis treatment to form free molecules in this study is expected to increase antioxidant activity. The antioxidant activity test used the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenger test. The value of Inhibitory Concentration 50% (IC50) obtained will show the antioxidant activity of the acid hydrolyzed water fraction of duwet (Syzigium cumini L.) leaf and the insoluble hexane fraction of jackfruit (Artocarpus heterophyllus) leaf acid hydrolysis. The results of the hydrolysis of the water fraction of duwet leaves and the insoluble fraction of jackfruit leaf hexane were measured for their antioxidant activity by DPPH radical scavenging test using UV-Vis spectrophotometer. To identify compounds in the water fraction and insoluble hexane fraction that act as antioxidants, qualitative analysis was used TLC and determined total phenolic compounds and flavonoids. The highest antioxidant activity of duwet leaves was in the hydrolyzed water fraction for 3 hours, while in jackfruit leaves the insoluble hexane fraction was hydrolyzed for 3 hours. Thus, the hydrolysis carried out in this study was able to increase the antioxidant activity.